2007
DOI: 10.1086/520961
|View full text |Cite
|
Sign up to set email alerts
|

A Homozygous Mutation in a Novel Zinc-Finger Protein, ERIS, Is Responsible for Wolfram Syndrome 2

Abstract: A single missense mutation was identified in a novel, highly conserved zinc-finger gene, ZCD2, in three consanguineous families of Jordanian descent with Wolfram syndrome (WFS). It had been shown that these families did not have mutations in the WFS1 gene (WFS1) but were mapped to the WFS2 locus at 4q22-25. A G-->C transversion at nucleotide 109 predicts an amino acid change from glutamic acid to glutamine (E37Q). Although the amino acid is conserved and the mutation is nonsynonymous, the pathogenesis for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
260
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(268 citation statements)
references
References 55 publications
4
260
1
1
Order By: Relevance
“…The causative genes for Wolfram syndrome, WFS1 and WFS2, encode transmembrane proteins localized to the ER (5,12,13). Mutations in the WFS1 or WFS2 have been shown to induce neuronal and β cell death.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The causative genes for Wolfram syndrome, WFS1 and WFS2, encode transmembrane proteins localized to the ER (5,12,13). Mutations in the WFS1 or WFS2 have been shown to induce neuronal and β cell death.…”
Section: Resultsmentioning
confidence: 99%
“…Insulin-dependent diabetes usually occurs as the initial manifestation during the first decade of life, whereas the diagnosis of Wolfram syndrome is invariably later, with onset of symptoms in the second and ensuing decades (7,10,11). Two causative genes for this genetic disorder have been identified and named Wolfram syndrome 1 (WFS1) and Wolfram syndrome 2 (WFS2) (12,13). It has been shown that multiple mutations in the WFS1 gene, as well as a specific mutation in the WFS2 gene, lead to β cell death and neurodegeneration through ER and mitochondrial dysfunction (5, 6, 14-16).…”
mentioning
confidence: 99%
“…We then considered other monogenic forms of syndromic diabetes, and selected genes that mapped to homozygous chromosome regions in the patient. This led us to select ALMS1, responsible for Alström syndrome, as a candidate gene; the ZCD2 gene, responsible for a rare variant form of WFS, 8 was located in a heterozygous chromosome region of the patient and was thus excluded. By sequencing of ALMS1 exons and flanking regions, we identified a homozygous T/G substitution in intron 18, located 3 bases before the start of exon 19 (IVS18-3 T4G, Figure 1a).…”
Section: Genetic Diagnosismentioning
confidence: 99%
“…Reported variants include a missense mutation in Jordanian families suggestive of a founder event and a deletion in one non-consanguineous Italian family. [2][3][4] There has been a suggested link between mitochondrial DNA mutations and WFS. 5 A 7.6-kb heteroplasmic deletion (spanning nucleotides 6465-14135) has been reported, 6 in addition to multiple deletions of mitochondrial DNA and a point mutation (m.3337G4A) in the mitochondrial gene encoding subunit ND1 in a Tunisian patient.…”
Section: Mutational Spectrummentioning
confidence: 99%
“…12 Patients with WFS2 have overlapping features with WFS1, plus defective platelet aggregation resulting in peptic ulcer bleeding, but importantly an absence of DI. 2,23 Children who are suspected of having WFS will undergo a number of investigations including MRI of the brain and orbit to look for generalised brain atrophy (cerebellum, medulla and pons), absence of signal from the posterior pituitary and reduced signal from the optic nerve. 24 Ancillary testing can be useful to confirm primary retinal ganglion cell dysfunction.…”
Section: Positive Clinical Predictive Valuementioning
confidence: 99%